RESPONSABILIDADE SOCIAL-CORPORATIVA COMO ORIENTAÇÃO ESTRATÉGICA EM ESCRITÓRIOS DE ADVOCACIA - Jorge, Fabiane Luisi Turisco (2011)
The legal segment represents a key sector, be it in politics or in the world. For this reason legal firms play an increasingly important role in a country‟s economic and social life. This dissertation is an attempt to rescue the pertinent social role of lawyers, mainly those associated with large and well-known law firms in Brazil, who preserve and even foster its economic development. As key social players these professionals are important opinion formers within our society. However, these players have lately been through a profound ethical crisis; working with the sole purpose of increasing their profit. They seem to be, most of the time, forgetful and disrespectful towards their constitutional duty to defend the collective interest of our nation. Nonetheless, indicating that change is upon us, there is a growing number of independent lawyers and leading law firms committed to social responsibility. Making use of these punch lines, whatever they may be, social practices developed by the 10 (ten) largest law firms of the country based on the law firms ranking of the magazine Análise Jurídica, Year 2009 it was possible to identify the social practices used, analyzing the level of involvement with their value chain, focusing on their interaction with 3 (three) stakeholders: client, employee and community. Based on this information, this dissertation is intended to direct law firms and lawyers to more mature and structured social practices. The objective is, through existing social practices and previously expressed interests, as well as through the incorporation of legal drivers into concepts exposed in the analysis of literature related to the sociology of the company and corporate social responsibility, to fuel the rethinking of social practices within law firms, encouraging corporate social responsibility as strategic guidance to the business. In this way it‟s established herein positions and possibilities for lawyers to be able to follow a path that is more in tone with constitutional determination and their vocation, offering relevant technical support to changes that are already impacting our society, aiming at playing the social role they were in fact trained to, without loosing focus on growth and profitability.